LOOTING: SEARCHING FOR THE CONTENT OF THE ACT (Bulletin of criminological association of Ukraine, 2023)
The article is devoted to the problem of doubtful legislative definition of such a relevant phenomenon as looting, liability for which is provided for in Article 432 of the Criminal Code of Ukraine. An attempt is made to identify the true meaning of the socially dangerous phenomenon under consideration on the basis of a brief etymological and semantic analysis, as well as with due regard for the comparative legal study of the relevant criminal law provisions of the legislation of some foreign countries.
Keywords: looting; military criminal offences; qualification of looting; active hostilities; servicemen, persons liable for military service; reservists, abduction